Pengaruh Penambahan EM4 dalam Fermentasi Solid Kelapa Sawit terhadap Kualitas Nutrisi Bahan Pakan: The Effect of EM4 Addition in Palm Oil Solid Fermentation on the Nutritional Quality of FeedIngredients - Saputri, Kade Wahyu; Nur’aini, Nur’aini; Suningsih, Nining; Hakim, Muhammad (Buletin Peternakan Tropis, 2025)
This study aims to evaluate the effect of the addition of Effective Microorganisms-4 (EM4) on changes in the proximate composition of palm oil solids during the fermentation process. The study design used EM4 treatments with different concentrations (0%, 0.5%, 1.0%, and 1.5% stored for 14 days. The parameters observed included moisture, ash, protein, fat, and crude fiber content. The results showed that moisture and ash content tended to decrease with increasing EM4 concentration and fermentation time. Protein content decreased significantly in the EM4 treatment compared to the control, indicating the utilization of organic nitrogen by microorganisms. Conversely, fat content increased in the 1.5% EM4 treatment, presumably due to the activity of lipolytic enzymes and microbial lipid biosynthesis. Crude fiber content showed a decreasing trend in the EM4 treatment, reflecting the degradation of cellulose and lignin by cellulolytic enzymes. Overall, the addition of EM4 can improve the nutritional quality of palm oil solids by reducing crude fiber and complex proteins and increasing the fat fraction at certain concentrations, so it has the potential to be used as an alternative feed ingredient for poultry